2017
DOI: 10.3906/bot-1606-12
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical survey in selected districts of the Black Sea region (Turkey)

Abstract: IntroductionTurkey has a rich floristic diversity and cultural heritage. Even though many scientific studies have explored the usage of wild plants for the purpose of treatment, foodstuff, or others, efforts carried out in this field are not adequate in documenting this kind of information because of the large surface area of the country and the richness of cultural heritage. In particular, factors such as increased migration from rural areas to urban areas, urbanization, increased coverage of health services,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
1
17
0
3
Order By: Relevance
“…Upson & S.Andrews W Turkish lavender, French lavender Flowering branches Infusion Baytop (1999) , Ertuğ (2004) , Arıtuluk (2010) Lamiaceae Lavandula stoechas L. CW Spanish lavender, topped lavender Leaves, Flowering branches Infusion Tuzlacı (2006) , Bulut and Tuzlacı (2015) , Sargin et al (2015a) , Özçelik et al (2016) , Bozyel and Merdamert-Bozyel (2020) Lamiaceae Marrubium rotundifolium Boiss. E Silver edged horehound Aerial parts Cataplasm Arıtuluk (2010) , Sargin et al (2015a) , Yeşilyurt et al (2017a) Lamiaceae Melissa officinalis L. CW Lemon balm Aerial parts Infusion Özhatay et al (2009) , Güneş (2017) , Demirci-Kayıran (2019) Lamiaceae Mentha longifolia (L.) L. W Horsemint, Asian mint Leaves Infusion Kilic and Bagci (2013) , Gökçe (2014) , Sargin et al (2015a) , Günbatan et al (2016) , Özçelik et al (2016) , Yeşilyurt et al (2017b) , Gürbüz et al (2019) Lamiaceae Mentha longifolia...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upson & S.Andrews W Turkish lavender, French lavender Flowering branches Infusion Baytop (1999) , Ertuğ (2004) , Arıtuluk (2010) Lamiaceae Lavandula stoechas L. CW Spanish lavender, topped lavender Leaves, Flowering branches Infusion Tuzlacı (2006) , Bulut and Tuzlacı (2015) , Sargin et al (2015a) , Özçelik et al (2016) , Bozyel and Merdamert-Bozyel (2020) Lamiaceae Marrubium rotundifolium Boiss. E Silver edged horehound Aerial parts Cataplasm Arıtuluk (2010) , Sargin et al (2015a) , Yeşilyurt et al (2017a) Lamiaceae Melissa officinalis L. CW Lemon balm Aerial parts Infusion Özhatay et al (2009) , Güneş (2017) , Demirci-Kayıran (2019) Lamiaceae Mentha longifolia (L.) L. W Horsemint, Asian mint Leaves Infusion Kilic and Bagci (2013) , Gökçe (2014) , Sargin et al (2015a) , Günbatan et al (2016) , Özçelik et al (2016) , Yeşilyurt et al (2017b) , Gürbüz et al (2019) Lamiaceae Mentha longifolia...…”
Section: Resultsmentioning
confidence: 99%
“…V.Engl. W No English name Flowers, Leaves, Barks Infusion, Decoction Saraç (2005) , Tuzlacı (2006) , Cansaran and Kaya (2010) , Gökçe (2014) , Bulut and Tuzlacı (2015) , Güner and Selvi (2016) , Uzun and Kaya (2016) , Maranki and Maranki (2016) , İşler (2017) , Karaköse and Karaköse (2017) , Köse (2019) Malvaceae Tilia tomentosa Moench CW European white lime, silver lime, silver linden Leaves, Flowers, Fruits, Barks, Bracts, Roots Infusion, Decoction Tuzlacı and Tolon (2000) , Tuzlacı and Eryaşar-Aymaz (2001) , Saraç (2005) , Özhatay et al (2009) , Sargin et al (2013) , Gökçe (2014) , Bulut and Tuzlacı (2015) , Akgül et al (2016) , Maranki and Maranki (2016) , Bulut et al (2017a) , İşler (2017) , Yeşilyurt et al (2017a , 2017b) , Guzel and Guzelsemme (2018) , Kurt and Karaoğul (2018) , Gürbüz et al (2019) Moraceae Ficus carica L. a CW Fig, common fig Fruits, Leaves Eaten after drying, Infusion Sargin et al (2013 , 2015a) , Köse (2019) Moraceae Morus alba L. CW …”
Section: Resultsmentioning
confidence: 99%
“…Besides, our country which hosted many civilizations has a rich cultural heritage and a wealth of ethnobotanical datas [13]. The traditional knowledge on plants and their uses has been disappearing in recent years because of urbanization, increased migration to urban areas, developments in technology, and health services easier accessibility [14][15][16] Therefore, any information about uses of the plant in our daily life should be recorded as soon as possible.…”
Section: Defect Of Melanin Synthesis Have Been Associatedmentioning
confidence: 99%
“…Ordu province has been located (40°18'-41°08' N, 36°52'-38°12' E) in Euro-Siberian phytogeographic region [17]. However There are the plenty of studies on the folk medicine in the Black Sea region, some of which is ethnobotanical research about Ordu, any study in Akkus district has not been found [9,14,[18][19][20][21][22][23][24][25][26]. Also, the effects of tyrosinase enzyme of the plants naturally growing in 35 villages of Akkuş District and used as folk medicine have been explored for the first time in this study.…”
Section: Defect Of Melanin Synthesis Have Been Associatedmentioning
confidence: 99%
“…Ülkemizin farklı illerinde yapılan çok sayıda etnobotanik çalışma mevcuttur. Düzce ilinde yapılan etnobotanik çalışmalar araştırıldığında üç çalışmaya rastlanılmıştır [2][3][4] ancak Düzce ilinin içinde yer aldığı Karadeniz Bölgesi'nde çok sayıda etnobotanik çalışma tamamlanmıştır [5][6][7][8][9][10][11]. Çalışma konumuz olan semt pazarlarında satışı yapılan bitkilerin etnobotanik kullanımlarına ilişkin olarak ise Hatay, Bingöl ve Kahramanmaraş illerinin semt pazarları ile ilgili hazırlanmış çalışmalar yapılmıştır [12][13][14].…”
Section: Introductionunclassified